Environmental Ethics. From theory to practical change - Peter Wolsing (Nordicum-Mediterraneum, 2016)
This paper provides a critical presentation of parts of Anglo-American environmental ethics from the perspective of the environmental crisis. Environmental ethics must attempt to provide the theoretical basis for overcoming the crisis to which it responds. So I suggest a possible connection of theory with practice by arguing that the meta-ethical approach to normativity via an axiology of nature should be supported by a theory like deep ecology that is dedicated to practical change. Naess’s notion of self-realization as an experiential process of gradual identification with all life contains the insight that practical change begins with a fundamental change of attitude.